APPLICATION OF MACHINE LEARNING AND NLP METHODS FOR ENHANCING PROFESSIONAL APTITUDE - Abutalipova, Н.Б.; Orazbekov, Ж.Н.; Nabiyeva, Г.С.; Smailova, Д.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article discusses the development and optimization of an artificial intelligence (AI)-based information system aimed at shaping learners' career aptitude. The relevance of using AI is justified in the context of dynamic changes in the labor market and the limitations of traditional career guidance methods. The proposed system architecture includes data collection models via an intelligent chatbot, market data analysis using NLP and clustering techniques, as well as methods for matching learners' profiles with professional requirements. Key AI technologies are described in detail, including natural language processing models (BERT, GPT, Llama), adaptive dialogue algorithms (decision trees, reinforcement learning), and matching methods (cosine similarity, Siamese networks). Special attention is given to the recommendation mechanism that integrates both compatibility and market demand criteria.